Soil Quality and Heavy Metal Source Analyses for Characteristic Agricultural Products in Luzuo Town, China - Zhaoyu Zhou; Zeming Shi; Linsong Yu; Haiyin Fan; Fang Wan (Agriculture, 2025)
Identifying the soil quality and the sources of heavy metals in the production areas of characteristic agricultural products is crucial for ensuring the quality of such products and the sustainable development of agriculture. This research took the farmland soil of Luzuo Town, a characteristic production area of Cangshan garlic in Linyi City, as the research object. The contents of Cr, Cu, Ni, Pb, Zn, As, Hg, and Cd in farmland soil were analyzed. The ecological risks were evaluated using the Geographical Cumulative Index (Igeo) and the Potential Ecological Risk Index. The spatial distribution characteristics of the elements were determined through geostatistical analysis, and Positive Matrix Factorization (PMF) was used for source apportionment. The results show the following: (1) The average concentrations of all heavy metals exceeded local background values, with Cr and Hg surpassing the screening thresholds from China’s “Soil Pollution Risk Control Standards” (GB 15618-2018). (2) The results of the Moran’s index show that, except for Hg and Cd, all the elements had a high spatial autocorrelation, and there are two potential highly polluted areas in the study area. (3) Soils were generally uncontaminated or low risk, with Hg and Cd as the primary ecological risk contributors. (4) Five sources were quantified: fertilizer and pesticide sources (32.28%); mixed sources of fertilizer, pesticides, and manure (14.15%); mixed sources of traffic activities and agricultural waste discharge (19.95%); natural sources (20.55%); and incineration sources (13.07%). This study demonstrates the value of integrating geospatial and statistical methods for soil pollution management. Targeted control of Hg/Cd and reduced agrochemical use are recommended to protect this important agricultural region.